2018
DOI: 10.3747/co.25.4036
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcome Measurement Compared with Professional Judgment of Cosmetic Results after Breast-Conserving Therapy

Abstract: Background In the present study, we set out to compare patient reported outcomes with professional judgment about cosmesis after breast-conserving therapy (bct) and to evaluate which items (position of the nipple, color, scar, size, shape, and firmness) correlate best with subjective outcome.Methods Dutch patients treated with bct between 2008 and 2009 were analyzed. Exclusion criteria were prior amputation or bct of the contralateral breast, metastatic disease, local recurrence, or any prior cosmetic breast s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…On the topic of long-term outcomes after reconstructive surgery, the literature contains few quantitative studies that rely on objective data. An important reason for this occurrence may be that postsurgical cosmesis—a large part of overall long-term outcomes—is extremely difficult to quantify objectively, and large discrepancies often exist between patient perception and physician assessment . Our study may be one of the earliest attempts to measure long-term postsurgical outcomes by quantifying it as the proportion of patients who requested or were offered a corrective measure.…”
Section: Discussionmentioning
confidence: 99%
“…On the topic of long-term outcomes after reconstructive surgery, the literature contains few quantitative studies that rely on objective data. An important reason for this occurrence may be that postsurgical cosmesis—a large part of overall long-term outcomes—is extremely difficult to quantify objectively, and large discrepancies often exist between patient perception and physician assessment . Our study may be one of the earliest attempts to measure long-term postsurgical outcomes by quantifying it as the proportion of patients who requested or were offered a corrective measure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that outcomes were scored differently by patients and professionals, and CRO and photographs might underestimate complications as compared with PROs 33 37. Sparano et al 3 systematically investigated the concordance between clinician-reported symptomatic adverse events (AEs) and information obtained via PROMs in 207 cancer RCTs, and found that 64.2% RCTs showed a discordance in AEs between PRO and CRO.…”
Section: Discussionmentioning
confidence: 99%
“…Sparano et al 3 systematically investigated the concordance between clinician-reported symptomatic adverse events (AEs) and information obtained via PROMs in 207 cancer RCTs, and found that 64.2% RCTs showed a discordance in AEs between PRO and CRO. Brands-Appeldoorn et al 37 showed agreement between professionals and patients about cosmetic outcomes was fair to moderate (intraclass correlation coefficients (ICC) range: 0.38–0.50). Other studies also confirmed that the overall concordance between clinicians and patients is low 38.…”
Section: Discussionmentioning
confidence: 99%
“…The poor quality of the scar is usually not a major problem (appearance, color, shape) [12] except in exposed regions (face) or when impacting the function (heel, eyelid, and periorificial areas).…”
Section: What Scarring Problems Are Usually Observed In the Elderly?mentioning
confidence: 99%